Transformation of Ma’pasilaga Tedong Gambling: Social And Economic Transformation In Toraja Cemetery Traditions - Tangkeliku, Agustinus Sem Porak; Saramae, Petrus Bine; Tandiangga, Patrio; Dama, Arwin; Palimbo, Hendrik (Universitas Negeri Medan, 2024)
In Tana Toraja and North Toraja, rambu solo’ is not only a funeral ceremony, but also reflects significant social changes. This article describes the transformation in Torajan society that is evident in the rambu solo’ ceremony. One interesting element is the buffalo fight (ma’pasilaga. tedong), which is now the main attraction in this ritual. This study was conducted using ethnographic methods. The study relied on participant observation and in-depth interviews. The results showed that each buffalo fight not only arouses the atmosphere, but also involves an increasingly growing element of gambling. In traditional practice, buffalo fights are held to entertain grieving families, adding meaning to the ritual. However, in recent times, gambling arenas have emerged in the ceremony, with betting on the outcome of the fights becoming commonplace. Ma’pasilaga tedong, conventional gambling, remains and attracts attention amid the increasing popularity of online gambling. This transformation shows how rambu solo’ has evolved into more than just a funeral ceremony, but also a new social and economic arena. As the Ma’pasilaga tedong arena and gambling become more dominant, this creates a new cultural mark in Torajan funeral traditions.